Comparison of resource use for farmed shrimp in Ecuador, India, Indonesia, Thailand, and Vietnam. Issue 1 (16th November 2021) - Boyd, Claude E.; Davis, Robert P.; McNevin, Aaron A.
Abstract: The purpose of this study was to assess the amounts of land, water, energy in fuels, and wild fish for fishmeal and fish oil in feeds required per tonne of harvested, farmed shrimp in five countries producing most of the shrimp destined for the international market. Land use for whiteleg shrimp Litopenaeus vannamei production differed slightly between Indonesia (0.37 ha/t shrimp) and the other four, major shrimp exporting countries – Ecuador, India, Thailand, and Vietnam (0.42–0.46 ha/t shrimp). Total water use was greater in Ecuador (76, 800 m 3 /t) and Indonesia (55, 000 m 3 /t) than in the other three countries (14, 000–45, 500 m 3 /t), but most water was saline. Freshwater use was mainly embodied in feed, did not differ among countries, and averaged 6.3% of total water use. Energy use ranged from 56.0 GJ/t (Ecuador) to 98.8 GJ/t (Thailand). All Asian countries had energy use above 75 GJ/t. Wild fish use for fishmeal and fish oil in feeds was greatest in Ecuador (0.891 t/t) and similar in Asian countries (0.612–0.670 t/t). In terms of edible crude protein, whiteleg shrimp was similar to broiler chickens, but more efficient than pigs and beef cattle in land and freshwater use, but greater in energy use than were the three terrestrial meat sources. Compared to L . vannamei, black tiger shrimp Penaeus monodon required more land, a greater amount of water, but less energy per tonne of shrimp. Although comparatively small differences in average uses of these primary resources were found among countries, the large variation which was noted among farms in each country suggests that resource use could be improved considerably.